Petani Sebagai Seorang Entrepreneur: Pengembangan Skill Petani Sebagai Aktor Penting dalam Sektor Pertanian - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Universitas Galuh, 2024)
This study aims to explain the definition of agricultural entrepreneurship and the skills that farmers must have for their agricultural development. Furthermore, this study tries to look at the obstacles faced by farmers and their implications for agricultural policy in general. This study used a literature study approach related to fruition, focusing interest on entrepreneurship and agricultural skills. In this study, researchers have provided an overview of the main topics in the agricultural entrepreneurship literature and suggested that some limited trends appear in the literature, such as the diversification of farming and agricultural entrepreneurship. The author found that there are some critical, reflective, and reflexive materials, and we see that there are some technical things that we take from the non-agricultural business sector for use in the agricultural sector, especially those related to developing the entrepreneurial capacity of farmers. The author concludes that the main challenge for the agricultural sector is to provide opportunities for farmers to be able to develop their entrepreneurial skills. This will certainly require support from various stakeholders, namely their role in providing coaching and mentoring for farmers, as well as opening economic access for farmers so that they can optimize their potential for farm development. It is hoped that this will be a contribution to this research for the agricultural sector in Indonesia.